STRUCTURING INTERDISCIPLINARY LEARNING USING TBL THROUGH PBL IN CARDIOVASCULAR DISEASES CASE UNIVERSITY OF ALGIERS - Drareni, Nasser (PUPIL: International Journal of Teaching, Education and Learning, 2019)
The study aims to show how can add a wide dimension to interdisciplinary learning using team-based learning (TBL) through problem-based learning (PBL) and facilitate the process of integration for cardiovascular disease (CVD) courses. However, the use of team-based learning through PBL as a pedagogical strategy also served to deepen learners’ understanding of CVD use real world problems in an undergraduate course of CVD. There were (60) preventive medicine learners who were selected and randomly divided into 2 groups: group 1 (n=30) with traditional teaching method and experimental group 2 (n=30) with team-based learning through PBL teaching methodology. The results of questionnaire showed that more than (90%) of experimental group learners thought team-based learning through PBL teaching approach could help to improve learning interest, independent thinking, and team collaboration. The most of learners had a positive attitude towards using team-based learning through PBL. To further their explanation of a topic or problem that needs two or more disciplines to solve problems related to risk factors of CVD. Learners combine, determine and develop information, concepts, methodologies and procedures from two or more disciplines to obtain deep knowledge, interpretation, abilities, and very often also to diagnose or solve real world problems. The perceptions of the university members for introduction of interdisciplinary learning using team-based learning through PBL at University of medicine Algiers were positive and encouraging. However, more workshops, online learning and virtual presentations emphasizing more on practical demonstrations were the felt need for successful structure of interdisciplinary learning.